Pecularities of reactive oxygen species accumulation in the primary culture of nerve cells of Lymnaea stagnalis - Haritonova, Valentina R.; Sidorov, Alexander V. (Experimental Biology and Biotechnology, 2021)
A fluorescent dye 2′,7′-dichlorodihydrofluorescein diacetate was used to characterize an accumulation of reactive oxygen species (ROS) in the primary culture (72 and 144 h) of neurons of the central ganglia of the mollusc Lymnaea stagnalis under conditions of acute, induced oxidative stress. It was found that larger cells accumulate a greater amount of ROS. High values of the relative (per unit area) fluorescence, indicating an increase in the amount of ROS per unit of intracellular space, are characteristic of smaller neurons of 72-hour culture. Changes in relative fluorescence over time are different from each other in neurons of 72- and 144-hour cultures. For an older culture, a negative, statistically significant relationship was noted (R = – 0.31), and for cells of 72 h of cultivation, a statistically significant correlation was not found (R = 0.12). It is assumed that the discovered relationship between the size (shape) of a neuron and its ability to resist the accumulation of ROS in the cytosol indicates differences in the resistance of CNS neurons to oxidative damage depending on their place and position in the neural network, thereby ensuring the selective stability of neuronal functions under conditions of oxidative stress.